The Relationship Of Learning Attitudes With Learning Outcomes - Handari, Eras Sahira; Gusnita, Wiwik; Syarif, Wirnelis; Andriani, Cici (Universitas Negeri Padang, 2024)
This research was motivated by the researcher's observations of students' poor learning attitudes in the food preparation subject, students' scores from the Mid-Semester Examination on average were still below the KKM. This research aims to describe learning attitudes, student learning outcomes, and analyze the relationship between learning attitudes and learning outcomes for class XI culinary students in the culinary subject at SMKN 6 Padang. This type of research uses a correlational descriptive method. The population in this study was class XI Culinary students at SMK N 6 Padang, totaling 101 students. Data collection was carried out by direct questionnaire and via Google Form using a Likert scale. Based on the results of statistical calculations, it can be seen that the learning attitudes of class The results of the hypothesis test obtained tcount > ttable, namely 4, 968 > 1.984 and a significance value of 0.001 <0.05. So it can be concluded that there is a significant relationship between learning attitudes and learning outcomes and the hypothesized results are (Ha) accepted.